2018
DOI: 10.1016/j.jsps.2018.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacy students’ perceptions towards online learning in a Saudi Pharmacy School

Abstract: Pharmacy students expressed some interest in online learning methods within the pharmacy curriculum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
43
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(44 citation statements)
references
References 19 publications
1
43
0
Order By: Relevance
“…About two third of the students agreed that face to face contact with teacher is necessary to learn (67.6%) and learning environment is better in college than at home (63.9%). These data suggest that nursing students prefer [18]. Similarly, a study also showed that majority (85%) of the student's preferred face to face teaching over e-teaching [15].…”
Section: Discussionmentioning
confidence: 78%
“…About two third of the students agreed that face to face contact with teacher is necessary to learn (67.6%) and learning environment is better in college than at home (63.9%). These data suggest that nursing students prefer [18]. Similarly, a study also showed that majority (85%) of the student's preferred face to face teaching over e-teaching [15].…”
Section: Discussionmentioning
confidence: 78%
“…These findings have previously been reported by Almaghaslah et al as students not fully understanding the concept of online education and preferring instructor-delivered face-to-face education. 7 Other aspects of online education that were not up to standard in the instructors' eyes included providing feedback and the delivery of practical and laboratory-based sessions.…”
Section: Discussionmentioning
confidence: 99%
“…King Khalid University (KKU) has adopted an online learning method along with traditional instructor-delivered dedicated lectures. 7 Both fully online learning and blended learning have been implemented. Online education at KKU is managed through the Blackboard learning-management system.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is because the applicants have a different background in ability and experience in using online technology, where some people could understand faster while some people could not, and this influences the acceptance and usage of MYeHalal system. When looking to similar studies that study humans interactions, acceptance, perceptions, and performance with online technology, there are many relatable studies, especially in online learning (Daʇhan and Akkoyunlu, 2016;Almaghaslah et al, 2018). As the online system is a technology used by many, studies pertaining its interaction with human being"s different abilities, needs, preferences, and outcomes are important to measure the efficiency of technology in meeting users" expectations.…”
Section: Literature Reviewmentioning
confidence: 99%